KEMAMPUAN MENULIS TEKS PERSUASI OLEH SISWA KELAS VIII-5 SMP NEGERI 4 MEDAN TAHUN AJARAN 2019/2020 - Sarifah Hanum (Universitas Islam Negeri (UIN) Sumatera Utara, 2021)
The results showed that the ability to write persuasive texts based on the aspect of issue recognition an average score of 71.7%, a series of arguments an average score of 74.16%, a statement of invitation an average score of 64.16%, reaffirmation an average score of 49 .6%, technical words score an average of 80.8%, and argumentative conjunctions score an average of 65.8%. So, the results show that grade VIII-5 students of SMP Negeri 4 Medan are categorized as sufficient in writing persuasive texts with the total average score of 66 and is in the sufficient category